Pengaruh Pengetahuan Perpajakan, Reformasi Perpajakan, Sanksi Perpajakan Dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak - Annisa Intan Herdiyanti; Hermi Hermi (Journal on Education, 2025)
This study aims to reveal the direct influence of tax knowledge, tax reform, tax sanctions and socialization on the level of taxpayer compliance. The object of the study is individual taxpayers registered at the Pasar Rebo Tax Office. This study was conducted using a quantitative descriptive method. Data collection was carried out through a questionnaire instrument. Data analysis used in this study include: multiple regression analysis (multiple linear regression), and classical assumption tests using the SPSS program. The results show that there is a significant simultaneous influence of Tax Knowledge, Tax Sanctions, and Tax Socialization on Taxpayer Compliance, but Tax Reform does not have a significant effect on Tax Compliance..